2018
DOI: 10.1016/j.nmni.2018.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Inventory and update on argasid ticks and associated pathogens in Algeria

Abstract: Argasid ticks include vectors of relapsing fevers caused by Borrelia spp. in humans, and they can transmit arboviruses and other bacterial pathogens. Knowledge about soft ticks (Ixodida: Argasidae) in Algeria is incomplete, and distribution data need to be updated. Here we report a series of entomologic investigations that we conducted in five different areas in Algeria between 2012 and 2015. Ticks were identified by entomologic keys and molecular tools (16S rRNA gene). Six distinct species belonging to two ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…A. persicus has adapted to parasitize fowl worldwide (28)(29)(30)(31), and in the present study, we found that domestic fowl of the selected districts were highly infested by this soft tick. Extremely elevated and low temperatures in the northern regions of KP, especially in district Chitral, might serve as less-favorable environmental conditions for the survival of A. persicus, a fact that has been observed in other parts of the world for soft ticks (32).…”
Section: Discussionsupporting
confidence: 66%
“…A. persicus has adapted to parasitize fowl worldwide (28)(29)(30)(31), and in the present study, we found that domestic fowl of the selected districts were highly infested by this soft tick. Extremely elevated and low temperatures in the northern regions of KP, especially in district Chitral, might serve as less-favorable environmental conditions for the survival of A. persicus, a fact that has been observed in other parts of the world for soft ticks (32).…”
Section: Discussionsupporting
confidence: 66%